DEVELOPMENT AND RESEARCH OF THE NANOMODIFIED FLUOROPLASTIC COVERAGES INFLICTED ON METALLIC SURFACES - OLEKSANDRENKO, Victor; SVIDERSRKYI, Vladislav; KIRICHENKO, Ludmila; DANILENKO, Igor; YEFYMENKO, Valerij (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Ways of increasing of physical and mechanical characteristics and wear resistance of fluoroplastic coatings on metal surfaces are analyzed. The influence of the composition and temperature-time conditions of the formation of multilayer fluoroplastic coatings on their adhesive strength, elasticity, shock resistance and abrasion resistance was studied. Primer layer for three-layer F-30P fluoropolymer coatings contained fluoropolymer F-30P - 72 wt. %, graphite C-1 - 25 wt. %, aminoorganosilica on the basis of aerosil - 3 wt. %.. The composition of the intermediate fluoropolymer layer: fluoropolymer F-30P - 79 wt. %, graphite C-1 - 20 wt. % aminoorganosilica based on aerosol - 1 wt. %. As the main task of applying the outer layer of fluoroplastic coating based on F-30P is to increase wear resistance, so its composition included1–3 wt. % ZrО 2 + 3% Y 2 O 3 (500 ˚C) or 1–3 wt. % ZrО 2 + 3% Y 2 O 3 (700 ˚C) or 1–3 wt. % zirconium hydroxide doped yttrium ions (the amount of yttrium in terms of oxides is 3 mol %): Zr(Y)O(OH) 2 and 17 wt. % graphite C-1, as well as 1 wt. % aminoorganosilica on the basis of aerosil. The analysis of the obtained results showed that the introduction of nanomodifiers of zirconium oxides encourages intense matrix structuring, as nanoparticles can create cluster-type ensembles. As a result a reinforced polymer system is created, which is characterized by increased strength and tribotechnical characteristics. Thus strength to scratch damage increased for three-layer fluoroplastic coatings, the outer layer of which includes: a) 17 wt. % graphite C-1 + 1 wt. % aminoorganosilica based on aerosil + 1 wt. % ZrО 2 + 3% Y 2 O 3 (500 ˚C) by 5.02 times, b) 17 wt. % graphite C-1 + 1 wt. % aminoorganosilica based on aerosil + 1 wt. % ZrО 2 + 3% Y 2 O 3 (700 ˚C) by 8.98 times, c) 17 wt. % graphite C-1 + 1 wt. % aminoorganosilica based on aerosil + 2 wt. % of zirconium hydroxide doped with yttrium ions (the amount of yttrium in terms of oxides is 3 mol %): Zr(Y)O(OH) 2 by 14.35 times compared to the unmodified fluoroplastic coating F-30 P. The modes of technological operations are described in detail. The properties of the developed coatings based on F-30P fluoropolymer are given. Features of formation of priming, intermediate and outer layers of fluoroplastic coating are outlined. The technology of nano-modified application of fluoroplastic coating by electrodeposition on metal surfaces has been developed. Therecommendations for using the results of the performed research for obtaining nanomodified fluoroplastic coatings with high adhesion to metal surfaces of the primer layer and wear resistance of the outer layer are given.